KONSEP KEBAHAGIAAN DALAM AL-QUR'AN: Kajian Tafsir QS. Al-Baqarah Ayat 216 dan Implementasinya dalam Kehidupan Sehari-hari - Rindu; Rahmayani; Wardinah; Zara; Edi Hermanto (AT-TAKLIM: Jurnal Pendidikan Multidisiplin, 2026)
Happiness is a primordial longing of every human being. The Qur'an, as a divine guide, provides a comprehensive concept of happiness that transcends ordinary human understanding. This study aims to examine the concept of happiness from a Qur'anic perspective, particularly through QS. Al-Baqarah verse 216, and to explore how this concept can be implemented in daily life. The method employed is thematic interpretation (tafsir maudhu'i) using a descriptive-analytical approach based on classical and contemporary scholarly interpretations. The findings reveal that happiness in the Qur'anic view is not synonymous with material pleasure alone, but encompasses total submission to Allah, contentment with His decree, and firm belief that behind every trial lies a profound wisdom. QS. Al-Baqarah 216 explicitly states that perhaps what one dislikes may be good for them, and what one loves may be harmful. When applied in daily life, this concept nurtures individuals who are grateful, patient, and optimistic in facing every trial.